Progressive Elastic-Resistance Training for Patellofemoral Pain Syndrome: Pain and Functional Movement Outcomes in Student Athletes - Samin, Giofandi; Ahmad Riady Hasibuan; Hendra Jaya (International Journal of Educational Research, 2026)
Patellofemoral pain syndrome is prevalent in active young adults and compromises participation and quality of life. This study examined the effectiveness of a pragmatic, six-week resistance band program on pain and functional movement in college students with patellofemoral pain syndrome. Using a one-group pretest–posttest design, participants completed three supervised sessions per week structured by a stabilization–strength–controlled power progression. Pain intensity was assessed with the Visual Analog Scale and functional movement with the Functional Movement Screen at baseline and post-intervention. The program produced large, statistically significant improvements: mean pain scores decreased markedly, and functional movement scores increased, indicating enhanced proximal stability, frontal-plane control, and movement efficiency. Effect sizes were very large for both outcomes, consistent with literature showing that targeted strengthening and neuromuscular training reduce patellofemoral joint stress and improve function. The intervention’s low cost, portability, and simple progression support scalability in resource-limited educational and community environments. While the design precludes definitive causal attribution, convergence of large effects across symptom and functional domains underscores the clinical promise of elastic resistance as a primary rehabilitation modality for patellofemoral pain syndrome. Future randomized studies should evaluate durability of benefits, dose–response characteristics, and mechanistic mediators using isokinetic, kinematic, and electromyographic assessments to optimize prescription and translation to sport-specific performance.